Safety of the proposed amendment of the specifications of the food additive steviol glycosides (E 960). (28th March 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion on the safety of proposed amendment of the specifications of the food additive steviol glycosides (E 960). The applicant asked to amend the existing EU specifications for steviol glycosides to allow for the inclusion of all steviol glycosides identified in Stevia rebaudiana Bertoni leaves, including both 'major' and 'minor' glycosides, that may comprise the assay value of not less than 95% total steviol glycosides. According to the applicant, all steviol glycosides are subject to microbial metabolism in a similar manner, ultimately generating the common primary metabolite steviol. There are uncertainties on the rate and extent of the metabolism of different steviol glycosides to steviol in the evidence provided and they did not allow the Panel to endorse the applicant's argumentation that all steviol glycosides generate the common metabolite steviol when subjected to microbial metabolism under realistic conditions. The available information was not sufficient to assess the safety of the proposed amendment of the specifications for E 960 and the conclusions on the previous assessments on steviol glycosides cannot be extrapolated to any other mixture of steviol glycosides (containing not less than 95% of any steviol glycosides) extracted from S. rebaudiana Bertoni leaves. Therefore, the Panel concluded that the submitted data were insufficient to assess the safety of proposed amendment of the specifications of the food additive steviol glycosides (E 960).